Simulation of the front and rear side illumination of the CdS/CIGS thin film solar cell - Pogrebnyak, A.D.; Rasheed, L.S.; Allohaibee, A.K.; Muhammed, A.K. (Физическая инженерия поверхности, 2011)
In this study the effect of the rear side illumination on the CdS/CIGS thin film solar cell has been studied. The simulation program SCAPS-1D was used in this study. This program was developed for the simulation properties of the CdS/CdTe and CdS/CIGS thin film solar cells. At the rear side illumination the efficiency of the cell decreased as the thickness of the CIGS absorber layer increased. This was because the light is absorbed far from the junction and near the high recombination back contact region. So that the generated electron-hole pairs are recombined before they reach the junction to separate. The losses in the generated electron-hole pairs increase as the thickness of the CIGS absorber layer increase and this is clearly shown in the variation of the quantum efficiency with the absorber thickness at the rear side illumination. В цьому дослідженні було вивчено вплив освітленості тильної сторони на тонкоплівкові сонячні елементи на основі CdS/CIGS. У дослідженні застосовувалася моделююча програма SCAPS-1D. Ця програма була розроблена для моделювання властивостей сонячних елементів на основі CdS/CdTe і CdS/CIGS. При освітленості тильної сторони ККД елементу знижується, оскільки збільшується товщина абсорбуючого шару CIGS. Це відбувається в результаті того, що світло поглинається далеко від переходу, біля області контакту до тильної поверхні. Внаслідок цього, утворені електронно-діркові пари рекомбінуються до того, як досягнуть переходу для розділення. Втрати утворених електронно-діркових пар збільшуються зі збільшенням товщини абсорбуючого шару CIGS, що чітко показано в зміні квантового виходу з товщиною абсорбуючого шару при освітленості тильної сторони. В данном исследовании было изучено влияние освещенности тыльной стороны на тонко-пленочные солнечные элементы на основе CdS/CIGS. В исследовании применялась моделирующая программа SCAPS-1D. Эта программа была разработана для моделирования свойств солнечных элементов на основе CdS/CdTe и CdS/CIGS. При освещенности тыльной стороны КПД элемента снижается, так как увеличивается толщина абсорбирующего слоя CIGS. Это происходит в результате того, что свет поглощается вдали от перехода, возле области контакта к тыльной поверхности. Вследствие этого, образованные электронно-дырочные пары рекомбинируются до того, как достигнут перехода для разделения. Потери образованных электронно-дырочных пар увеличиваются с увеличением толщины абсорбирующего слоя CIGS, что четко показано в изменении квантового выхода с толщиной абсорбирующего слоя при освещенности тыльной стороны.